Praktik Mengajar Mahasiswa Pendidikan Agama Islam Menggunakan Metode Active learning Untuk Meningkatkan Antusiasme Belajar Peserta Didik di Madrasah Tsanawiyah Tholabuddin Masin, Kecamatan Warungasem, Kabupaten Batang. - Ryan Deriansyah; Fitria Nurmala Sari; Rofiqoh; Irkham Nur Salim; Muhammad Rizan Faqih; Maulana Zidni; Shinta Dewi Qomariyah; Indah Rakhmawati; Riza Risqyana; Aisyah Nanda Ramdhaniya (Presisi Jurnal Pengabdian Masyarakat, 2022)
Abstrak: Field Experience Practice (PPL) or teaching practice is one of the courses that must be followed by every teacher student, including Islamic Religious Education students. The teaching practice program is organized so that students can practice the theory gained during lectures so that they acquire special skills in accordance with their expertise in the teaching profession. Teaching Practice Activities of PAI Students Through Active Learning Methods at Madrasah Tsanawiyah Tholabuddin Masin. Activities in this service use the Applied Research method. In the teaching practice carried out by students of UIN KH. Abdurrahman Wahid Pekalongan at MTs. Tholabuddin uses a student-centered approach that focuses on students. And the method used is active learning. Some of the methods or strategies used include: throwing puzzles, Team Games Tournament, Domino SKI, and Short Cards.)